2015
DOI: 10.1016/j.exphem.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of glycans, related genes, and proteins in two human bone marrow stromal cell lines using an integrated strategy

Abstract: Altered expressions of glycans is associated with cell-cell signal transduction and regulation of cell functions in the bone marrow microenvironment. Studies of this microenvironment often use two human bone marrow stromal cell lines, HS5 and HS27a, co-cultured with myeloid cells. We hypothesized that differential protein glycosylation between these two cell lines may contribute to functional differences in in vitro co-culture models. In this study, we applied an integrated strategy using genomic, proteomic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Based on our in vitro observations, we intravenously co-injected HS5 cells and MDS marrow-derived hematopoietic cells into Nod.cg-Prkdc scid Il2rg tm1wjll (NSG) mice, and observed that differential stromal contact had structural and functional effects on proliferation of MDS precursor cells [40]. Also, we used glycomics (lectin microarray) and proteomics (SILAC method) approaches to compare two bone marrow stromal cell lines, HS5 and HS27a, and observed differential expression of several glycans and proteins [18, 41]. These and many similar findings indicate that microenvironmental factors play key roles in both normal and pathological hematopoiesis, and that hematopoiesis is modulated by bidirectional signals between hematopoietic cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our in vitro observations, we intravenously co-injected HS5 cells and MDS marrow-derived hematopoietic cells into Nod.cg-Prkdc scid Il2rg tm1wjll (NSG) mice, and observed that differential stromal contact had structural and functional effects on proliferation of MDS precursor cells [40]. Also, we used glycomics (lectin microarray) and proteomics (SILAC method) approaches to compare two bone marrow stromal cell lines, HS5 and HS27a, and observed differential expression of several glycans and proteins [18, 41]. These and many similar findings indicate that microenvironmental factors play key roles in both normal and pathological hematopoiesis, and that hematopoiesis is modulated by bidirectional signals between hematopoietic cells and the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar enrichment of genes of glycan biosynthesis pathway is suggestive of their crucial role in cell adhesion, differentiation, cell survival, and signal transduction processes. 34 Several studies have shown that tolerance (induced, operational, immunologic, or "prope") was accomplished through activation and differentiation of B cell subtypes and regulatory T cells. 11,[35][36][37][38][39][40][41][42] However, these studies were mostly limited to analysis of gene expression profiles in the PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Human marrow stromal cell lines HS27a and HS5 have been used in studies of MDS as well as various types of cancer. We previously characterized glycan expression levels in these two cell lines using an integrated strategy combining gene microarray, proteomic, and lectin microarray analyses [33]. However, integrated analysis using differential genomic and proteomic techniques has not yet been performed.…”
Section: Discussionmentioning
confidence: 99%